Fuzzy Reasoning untuk Analisa Keterkaitan Hubungan Jurusan di Sekolah Menengah Atas dengan Kemampuan Programming Mahasiswa - Sri Mulyati; Endar Nirmala (Teknik Informatika Universitas Pamulang, 2021)
Programming is one of the skills which is very important today, especially in the Internet of Things (IoT) technology. Applications are the top layer of IoT, so the capability of application creation is most important. The basis for making applications is an algorithm related to logic, namely the ability to solve problems. Currently, students' logic and programming skills are still very lacking by a percentage of 10% - 15% per class for a total of 35 people. Secondary education background is a provision for students in the college process. And students' secondary education backgrounds vary, such as science, social studies, accounting, automotive, RPL, Multimedia, TKJ, etc. If the informatics study program wants to get graduates with good abilities, it is necessary to consider a suitable educational background. The above is the basis of this research, namely knowing the influence of high school students' majors on their programming abilities. The method for this problem uses Fuzzy Reasoning. This method can solve problems that are uncertain or fuzzy with an approach to existing problems or data. The stages of the method are input (crisp), fuzzification, inference, defuzzification, and output (crisp). The data to be used are majors and two grades from subjects related to logic according to majors. The algorithm that be used in the Fuzzy Method is Mamdani. The output of the defuzzification is the value level of the majors in the Hight Scholl or Vocational School. Those are the order of most suitable for the Informatics Engineering Study Program (IT Study Program). The values obtained are processed using fuzzy similarity to get the similarity value or case suitability. The application of the method in this study resulted in the suitability value of the high school / vocational majors with the informatics engineering study program of 51.97%. It means that the student background is not suitable for the informatics engineering study program. While the accuracy rate is 63.46%.